2021
DOI: 10.1101/2021.07.14.452299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CIITA induces expression of MHC-I and MHC-II in transmissible cancers

Abstract: MHC-I and MHC-II molecules are critical components of antigen presentation and T cell immunity to pathogens and cancer. The transmissible devil facial tumour (DFT) cells that cause Tasmanian devil facial tumour disease (DFTD) exploit MHC-I pathways to overcome immunological anti-tumour and allogeneic barriers. This exploitation underpins the ongoing transmission of DFT cells across the wild Tasmanian devil population. MHC-II expression is crucial for CD4+ T cell activation and is primarily confined to haematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Our results using IFN-γ expressed via a human adenovirus agree with previous studies showing that IFN-γ strongly upregulates β2m on devil facial tumour cells [6,35,36]. More recently, genetically modified DFT1 cells that either constitutively upregulate β2m or have β2m knocked out have been used to conclusively show that MHC-I is a major target in immunotherapyinduced DFT1 regressions and rare cases of natural DFT1 regressions [7,10,37,38]. Our results here using the Ad5-IFN-γ vector open the door to relatively low-cost immunotherapy to potentially treat devils with DFT1 or DFT2.…”
Section: Resultssupporting
confidence: 90%
“…Our results using IFN-γ expressed via a human adenovirus agree with previous studies showing that IFN-γ strongly upregulates β2m on devil facial tumour cells [6,35,36]. More recently, genetically modified DFT1 cells that either constitutively upregulate β2m or have β2m knocked out have been used to conclusively show that MHC-I is a major target in immunotherapyinduced DFT1 regressions and rare cases of natural DFT1 regressions [7,10,37,38]. Our results here using the Ad5-IFN-γ vector open the door to relatively low-cost immunotherapy to potentially treat devils with DFT1 or DFT2.…”
Section: Resultssupporting
confidence: 90%
“…The data are provided in the electronic supplementary material [77]. Conflict of interest declaration.…”
mentioning
confidence: 99%
“…This is hypothesized to play a key role in the absence of MHC-I on the surface of DFT1 cells. However, MHC-I can be upregulated following stimulation with interferon gamma (IFNG) (11,13,14). Subsequent studies identified MHC-I as a primary antibody target in immunotherapy-induced and rare cases of naturally occurring DFT1 tumor regression (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%